2017
DOI: 10.1061/(asce)ee.1943-7870.0001255
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-Scale Decontamination of Soil Polluted with As, Cr, Cu, PCP, and PCDDF by Attrition and Alkaline Leaching

Abstract: Recently, an efficient and promising process was developed to allow the removal of As, Cr, Cu, pentachlorophenol (PCP), and 7 polychlorodibenzo-dioxins and furans (PCDDF) from soil using alkaline leaching. The present study evaluates the performance and the 8 robustness of this decontamination process for the treatment of four different polluted soils by attrition and alkaline leaching at a pilot scale. 9The attrition process carried out on the coarse fraction (>0.125 mm) allowed the removal of 24-42% of As, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Over the past several decades, several authors have studied physical and chemical decontamination processes to evaluate their ability to simultaneously remove inorganic and organic compounds from solid matrices, including soils (Riveiro-Huguet and Marshall, 2011;Bisone et al, 2013a;Reynier et al, 2013a, b;Guemiza et al, 2016;Metahni et al, 2016). The attrition uses high-intensity agitation to remove films around soil particles and/or to detach fine particles from the surface of coarse particles, resulting in the release of contaminants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past several decades, several authors have studied physical and chemical decontamination processes to evaluate their ability to simultaneously remove inorganic and organic compounds from solid matrices, including soils (Riveiro-Huguet and Marshall, 2011;Bisone et al, 2013a;Reynier et al, 2013a, b;Guemiza et al, 2016;Metahni et al, 2016). The attrition uses high-intensity agitation to remove films around soil particles and/or to detach fine particles from the surface of coarse particles, resulting in the release of contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…The attrition process is governed by the physical contact between the contaminated particles themselves, the contact between the contaminated particles and the liquid phase, and the walls and the impellers present in the mixing reactor, which favor the removal of the fine particles that contain the contaminants. As most of the contaminants present in soil usually have low water solubility, such additives as acids, alkaline agents, surfactants and/or chelating agents are often added into the attrition pulp to improve the removal of both inorganic (e.g., As, Cr, Cu, Pb, and Zn) and organic compounds (e.g., PAHs, PCP, and PCDDFs) (Riveiro-Huguet and Marshall, 2011;Bisone et al, 2013a;Reynier et al, 2013b;Guemiza et al, 2016;Metahni et al, 2016). Surfactants are compounds that contain both hydrophilic and hydrophobic parts in their molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…Another parameter that could influence the performance of an attrition process is the stirring speed. A study carried out at room temperature showed that three attrition steps of 20 min each performed at 1,700 rpm with a pulp density fixed at 40% (w/w) allowed the removal of 24 -42% of As, 0 -13% of Cr, 23 -46% of Cu, 0 -85% of PCP and 17 -64% of PCDD/F from the coarse particles (> 0.125 mm) of contaminated soils (Metahni et al 2016). The attrition tests carried out by Bayley et al (2005) with an aqueous suspension of contaminated soil showed that the speed of the impeller had a significant effect on the removal of contaminants.…”
Section: Temperature and Stirring Ratementioning
confidence: 99%
“…Bisone et al (2013) removed more than 90% of PAHs from soils using attrition in the presence of a surfactant ([Cocamidopropyl Hydroxysultaine, CAS] = 0.2 g.L -1 ). Metahni et al (2016) found that three attrition steps (PD = 40%, T = 25°C, 1-4 mm soil fraction) allowed the removal of 60% and 97% of PCP with and without the addition of surfactant (cocamidopropylbetaine, BW) at 1% (w.w -1 ), respectively. Recently, Guemiza et al (2016) showed that the concentration of the surfactant BW (0 -3%, w.w -1 ) was the main parameter influencing the removals of both PCP and PCDD/F from the 1-4 mm soil fraction by attrition (PD = 40%, T = 25°C, t = 20 min, 5 attrition steps), using an experimental design methodology.…”
Section: Surfactant Concentrationmentioning
confidence: 99%
See 1 more Smart Citation